2010
DOI: 10.1007/s12598-010-0030-6
|View full text |Cite
|
Sign up to set email alerts
|

Wear characteristics of spheroidal graphite roll WC-8Co coating produced by electro-spark deposition

Abstract: Electro-spark deposition (ESD) was adopted for preparing high property coatings by depositing WC-8Co cemented carbide on an spheroidal graphite roll substrate. The microstructure and properties of the coating were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM) with energy dispersive X-ray (EDX) and ball-disc configuration wear tester. The results show that nanosized particles and amorphous structures prevail in the coating which is metallurgically bonded to the substrate. The micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The use of ESD to restore oxidation resistant coatings by Farhat and Brochu (2012), found that the performance of the repaired coating was improved due to the fine grain structure of the deposited material, which allowed for improved diffusion along the grain boundaries. Improved tribological properties (increased wear resistance) of nanoscale structured ESD WC-Co coatings have also been reported in the literature (Wang et al, 2010).…”
Section: A C C E P T E D Mmentioning
confidence: 61%
“…The use of ESD to restore oxidation resistant coatings by Farhat and Brochu (2012), found that the performance of the repaired coating was improved due to the fine grain structure of the deposited material, which allowed for improved diffusion along the grain boundaries. Improved tribological properties (increased wear resistance) of nanoscale structured ESD WC-Co coatings have also been reported in the literature (Wang et al, 2010).…”
Section: A C C E P T E D Mmentioning
confidence: 61%
“…Several authors have shown that the hardness of the deposits was generally higher than that of the substrate regardless of the depositing parameters. In particular, they reported that the microhardness of the coatings gradually decreased from the coating top surface to the substrate [49,[92][93][94]. As shown above, the higher hardness value of the ESD coatings compared with that of the substrate is mainly due to the formation of the fine microstructure induced by rapid solidification.…”
Section: Amorphous Depositsmentioning
confidence: 85%
“…Additionally, the wear resistance of the coatings is related to the hardness. The tribological performance of an ESD coating depends on the distribution, size, and morphology of the particles present in the deposit as well as the coating thickness [92]. Generally, the main wear mechanisms found are: fatigue wear, adhesive wear, oxidation wear in different conditions, and abrasive wear.…”
Section: Amorphous Depositsmentioning
confidence: 99%
“…One of the advantages of hard alloy coatings is their high wear resistance [15][16][17] and therefore this characteristic was determined for the obtained electrospark coatings deposited during 5 min at a frequency of 100 Hz. The wear testing showed that the wear resistance of all cathode surfaces modified by the electrospark treatment with the use WC-Co-C electrodes increased by a factor of four or more in comparison with the steel substrate.…”
Section: Mechanical Properties Of Coatingsmentioning
confidence: 99%